Factors Associated with the Use of Helicopter Inter-facility Transport of Trauma Patients to Tertiary Trauma Centers within an Organized Rural Trauma System. (2nd September 2016) - Stewart, Kenneth; Garwe, Tabitha; Bhandari, Naresh; Danford, Brandon; Albrecht, Roxie
Abstract: Objective: A review of the literature yielded little information regarding factors associated with the decision to use ground (GEMS) or helicopter (HEMS) emergency medical services for trauma patients transferred inter-facility. Furthermore, studies evaluating the impact of inter-facility transport mode on mortality have reported mixed findings. Since HEMS transport is generally reserved for more severely injured patients, this introduces indication bias, which may explain the mixed findings. Our objective was to identify factors at referring non-tertiary trauma centers (NTC) influencing transport mode decision.Methods: This was a case-control study of trauma patients transferred from a Level III or IV NTC to a tertiary trauma center (TTC) within 24-hours reported to the Oklahoma State Trauma Registry between 2005 and 2012. Multivariable logistic regression was used to determine clinical and non-clinical factors associated with the decision to use HEMS.Results: A total of 7380 patients met the study eligibility. Of these, 2803(38%) were transported inter-facility by HEMS. Penetrating injury, prehospital EMS transport, severe torso injury, hypovolemic shock, and TBI were significant predictors (p<0.05) of HEMS use regardless of distance to a TTC. Association between HEMS use and male gender, Level IV NTC, and local ground EMS resources varied by distance from the TTC. Many HEMS transported patients had minor injuries and normal vital signs.Conclusions: Our results suggest that while distance remains the most influential factor associated with HEMS use, significant differences exist in clinical and non-clinical factors between patients transported by HEMS versus GEMS. To ensure comparability of study groups, studies evaluating outcome differences between HEMS and GEMS should take factors determining transport mode into account. The findings will be used to develop propensity scores to balance baseline risk between GEMS and HEMS patients for use in subsequent studies of outcomes.